An Analysis of Role Play Technique in Students’ Interpersonal Skill at Universitas Muhammadiyah Makassar - Farisha Andi Baso (BATARA DIDI : English Language Journal, 2023)
This research is undertaken to increase students’ interpersonal speaking skill at the third semester students in Universitas Muhammadiyah Makassar through role play technique. The researcher employed a Classroom Action Research (CAR) which is conducted to tackle the students’ problem in English speaking. The Classroom Action Research (CAR) was done based on Kurt Lewin’s concept. The researcher conducted two cycles in which each cycle consists of planning, acting, observing, and reflecting. The data were acquired by qualitative and quantitative data. The qualitative data were collected by examining the observation outcome. Then, quantifiable data were acquired from the students’ speaking score pre-test and post-test. The finding of this study suggested that the deployment of role play approach was successful since the criteria of success were achieved. The first criterion was 75% of pupils could pass the target ≥ 65 based on the KKM. The finding showed that 83.33% of pupils had already obtained the goal score. Besides, the second criterion was the pupils who become more active involved in teaching learning process. The outcome of observation showed that by employing role play technique were engaged participating in the classroom.